Business Model Innovation Process on the Example of an IT Company - Fokczyński, Wojciech (Modyfikacja modelu biznesowego na przykładzie firmy z branży IT, 2024)
The aim of the article is to explore one of the business model transformation processes in the XYZ company, operating in the ERP systems industry. This company, in order to repair internal problems, as well as strengthen its position on the market, decided to change the business model by adding a new business line, which introduced the company to the education industry. In order to achieve the aim of the article, an Individual In-depth Interview (IDI) and a review of the company’s internal documentation were conducted. The article ends with conclusions and recommendations connected with Business Model Innovation (BMI). They describe factors conducive to modifying business models and the concept of complementarity developed on the basis of literature analysis and the results of in-depth interviews.
Fokczyński, W. (2024). Business Model Innovation Process on the Example of an IT Company. W J. Radomska & A. Witek-Crabb (Red.), New Trends in Business Management (s. 118–135). https://doi.org/10.15611/2024.30.7.09
Keywords: business model; business lines; business model modification; IT; strategy and business model; Business Model Innovation; model biznesu; linia biznesowa; modyfikacja modelu biznesowego; strategia a model biznesowy